Social policy in economic development: The case of health and old age insurance - Rainer Thiele (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1997)
This paper analyzes possible justifications for government interventions in health and old age insurance and illustrates the theoretical considerations by the case of Chile where a comprehensive social sector reform took place in the 1980s. It is shown that health insurances can suffer from adverse selection and risk selection as well as from moral hazard. In dealing with adverse selection and risk selection, governments can choose between social insurance and regulated private insurance, depending on the relative weight given to equity and efficiency. The problem of moral hazard can be diminished by various supply and demand side cost-sharing devices. With respect to old age security, the case for the system of forced savings prevailing worldwide mainly relies on the hypothesis that people tend to undersave for retirement. Among the possible pension schemes, funded systems are likely to have advantages over PAYG systems in that they improve efficiency.
Keywords: 330; Krankenversicherung; Gesundheitsreform; Adverse Selection; Moral Hazard; Gesundheitskosten; Welt; Entwicklungsländer; Chile